Chihera in Zimbabwe
XVII, 355 p. 13 illus.
Keywords: Zimbabwean social media has been awash with images of a woman character, spirit, or concept called Chihera. Traditionally, a woman descending from the Mhofu (Eland) lineage/totem is known as Chihera. In the cumulative tradition of the Shona (a Zimbabwean ethnic group), Chihera is a fiercely independent, assertive, free spirited, and no nonsense woman. This volume seeks to deepen reflections on the Chihera phenomenon in the context of the search for gender justice in Zimbabwe and Africa. The authors reflect on how this radical indigenous feminist ethic circulating on social media can animate the quest for Zimbabwean and African women’s full liberation from patriarchy and all oppressive forces. They grapple with the issue of generating culturally sensitive theories and approaches to galvanize the struggle for African women’s liberation in post-colonial settings. Second, they locate the Chihera mystique in the context of the practical struggle for women’s empowerment.Third, the volume illustrates how the Chihera phenomenon could be utilized for gender justice in Zimbabwe and beyond. Ezra Chitando is Professor of History and Phenomenology of Religion and World Council of Churches Theology Consultant on HIV and AIDS in Africa. Sophia Chirongoma is a senior lecturer in the Religious Studies Department at Midlands State University, Zimbabwe. She is also an academic associate/research fellow at the Research Institute for Theology and Religion (RITR) at UNISA. Munyaradzi Nyakudya is a senior lecturer in the History, Heritage and Knowledge Systems Department at the University of Zimbabwe. He has research interests in, among other areas, history, ethnomusicology, and human security.